# Thread: Finding equation of normal to a curve.

1. ## Finding equation of normal to a curve.

Well I got this question:

Differentiate from first principals (i did it) $f=x^3$ $f'(x) = 3x^2$

Find the equation of the normal to the curve at point where x = 3.

So first I found y. $y=(3)^3 y=27$ That means we got $(3,27)$

Then I subbed 3 into $3x^2$ to get the gradient of the tangent. Answer is $27$

Since the normal and tangent are perpendicular the formula is $m_{2} = \frac {-1}{m_{1}}$ So that makes $\frac {-1}{27}$

Then I subbed it into $y-y_{1} = m(x-x_{1}$

$y-27=\frac{-1}{27}(x+3)$

Finally I get

$-27y+726=x+3$ but for some reason the answers in the book says it's different

Did I do anything wrong?

Also, I need help with another question:

If $y=x^3-3x^2$ find the derivative and find the values of y when $\frac{dy}{dx} = 0$

How would I go about starting this one?

2. Originally Posted by jgv115
Well I got this question:

Differentiate from first principals (i did it) $f=x^3$ $f'(x) = 3x^2$

Find the equation of the normal to the curve at point where x = 3.

So first I found y. $y=(3)^3 y=27$ That means we got $(3,27)$

Then I subbed 3 into $3x^2$ to get the gradient of the tangent. Answer is $27$

Since the normal and tangent are perpendicular the formula is $m_{2} = \frac {-1}{m_{1}}$ So that makes $\frac {-1}{27}$

Then I subbed it into $y-y_{1} = m(x-x_{1})$

$y-27=\frac{-1}{27}(x-3)$ <=== you used the wrong sign in the bracket

Finally I get

$-27y+726=x+3$ but for some reason <=== maybe they believe that 27² = 729
the answers in the book says it's different

Did I do anything wrong?

Also, I need help with another question:

If $y=x^3-3x^2$ find the derivative and find the values of y when $\frac{dy}{dx} = 0$

How would I go about starting this one?
To your last question: I know that you know how to find the drivatie: Differentiate y wrt x. Solve the equation for x:

$3x^2-6x = 0$

3. Originally Posted by earboth
To your last question: I know that you know how to find the drivatie: Differentiate y wrt x. Solve the equation for x:

$3x^2-6x = 0$
mm what do you mean i put the wrong sign? I'm pretty sure x is 3.

What does y wrt x mean?

4. It's actually the next step which is wrong, since when you multiply both sides by $-27$ you should get

$-27y + 729 = x - 3$.

"wrt" means "with respect to". So Earboth is saying find $\frac{dy}{dx}$.

5. Originally Posted by Prove It
It's actually the next step which is wrong, since when you multiply both sides by $-27$ you should get

$-27y + 729 = x - 3$.

"wrt" means "with respect to". So Earboth is saying find $\frac{dy}{dx}$.
Yea, I actually typed it wrong.

I was meant to type:
$-27y + 726 = x$. I got 729 then I had to subtract 3 and i get 726. The answer says it's 732 though :S

And why do you have the equate the $\frac {dy}{dx}$ to 0?

$3x^2-6x = 0$

$3x(x-2) =0$

$x = 0$ $x= 2?$

6. Because that's what you were told to do in the question...

You have found the $x$ values of the stationary points, now substitute back into the original function to find the corresponding $y$ values.

7. y=0 and y=4

yay!

8. Originally Posted by jgv115
Yea, I actually typed it wrong.

I was meant to type:
$-27y + 726 = x$. I got 729 then I had to subtract 3 and i get 726. The answer says it's 732 though :S

And why do you have the equate the $\frac {dy}{dx}$ to 0?

$3x^2-6x = 0$

$3x(x-2) =0$

$x = 0$ $x= 2?$
Like I said, you should have

$-27y + 729 = x - 3$.

Now you have to ADD 3 to both sides (to undo the -3 ) which gives

$-27y + 732 = x$ as required.

9. yea i get it!! (stupid mistake)